Material Selection for Aeronautical Structural Application - Lopes,Julio C. O. (2008)
The use of different materials as metals, wood and other modern materials like composites, require a previous evaluation of its performance under corrosion, creep, tension, compression, bending and fatigue. In general, these requirements lead to a few number of materials to choose during the project of one component, but in some cases, theres a lot of options that can be selected. In this work, a mechanical approach is considered for some classes of materials. Of course, a complete analysis involves a management science, also called, operational research, with an application of linear programming or, in some cases, heuristics models like ants colony, but this isnt our target at this moment. Its possible to see, with the mechanical approach, the advantage of composites materials application.